If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying B = 5A + 4C Solving B = 5A + 4C Solving for variable 'B'. Move all terms containing B to the left, all other terms to the right. Simplifying B = 5A + 4C
| (5/x)=(6/x^2)+1 | | -2(r+4)=-27 | | .4(3z+6)+20.4=.7(3z-6) | | 5/x=6/x^2+1 | | A=5B+4C | | x-2x+y/y | | 28-19= | | (2x+32)+6=x+26 | | t^2=6-t | | .3x-1=.1(x+10) | | f(4)=4+9.5 | | 3/10=x/2730 | | 1/m+1/2m=1/6 | | 2(2x+3)+2x=37 | | 7+5n=3n+5 | | x+x+3=5-2(x-5) | | 5/6y=7-11/12y | | x-6-(10x-8)= | | 3+8q=6+7q | | -3a-8(-5a-1)= | | 4p^2+164p+81=0 | | (3x-9)=(2x+31) | | B-4+6b=23 | | 1/6-3x/2=x/4-1/4 | | 3x-4(x+2)=3(4-2x)+8 | | 3/2=21/x | | 3x-1/2x | | b+.66666=2 | | f(1/2)=1/2+9.5 | | -17+20= | | -6(v-4)=18-5v | | x/6-x/12+8=x+8 |